2021
DOI: 10.4309/jgi.2021.48.8
|View full text |Cite
|
Sign up to set email alerts
|

Safer by design: Building a collaborative, integrated and evidence-based framework to inform the regulation and mitigation of gambling product risk

Abstract: Evidence suggests that harms may result from gambling participation as a result of a complex interaction between individual differences among consumers, environmental factors, and the characteristics of the gambling product. The latter of these factors, broadly referred to in this paper as product risk, has received increased policy attention in recent years. Product-focussed approaches to harm reduction, however, are under-developed relative to other forms of player protection and likely reflects the limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…As these factors are specifically engendered by the digital environment, and thus are not an issue in relation to physical pack consumption, it highlights arguments as to why regulators do not view physical booster packs as having the addictive potential of digital loot boxes. This interpretation is consistent with research from the field of gambling studies which has found that digital versions of scratch-cards and instant-win lotteries are more problematic than their physical counterparts [29]. Indeed, online environments afford increased ease of access to digital products and services than to physical ones, greater event frequency, and the rapid reinvestment of any <winnings=, thereby giving rise to increased potential for problematic consumption behaviors to develop [40,131].…”
Section: Discussionsupporting
confidence: 84%
“…As these factors are specifically engendered by the digital environment, and thus are not an issue in relation to physical pack consumption, it highlights arguments as to why regulators do not view physical booster packs as having the addictive potential of digital loot boxes. This interpretation is consistent with research from the field of gambling studies which has found that digital versions of scratch-cards and instant-win lotteries are more problematic than their physical counterparts [29]. Indeed, online environments afford increased ease of access to digital products and services than to physical ones, greater event frequency, and the rapid reinvestment of any <winnings=, thereby giving rise to increased potential for problematic consumption behaviors to develop [40,131].…”
Section: Discussionsupporting
confidence: 84%
“…Allsopp (2021) opines that algorithms are used to correct individuals' behaviours so that they selfregulate and are shaped into a productive population of "responsible gamblers". The debate over the best approach to responsible gambling -i.e., individual responsibility vs. public health -remains a contested debate amongst stakeholders (Delfabbro et al, 2021), and the role of AI warrants inclusion in these discussions.…”
Section: Exploitationmentioning
confidence: 99%